Correlation Between Child’s Gender, Birth Weight, Maternal Age, and Stunting Risk Under Five: A Systematic Review - Tya Wahyun Kurniawati; Esti Yunitasari; Iqlima Dwi Kurnia (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting is a problem that threatens human quality in the world. Apart from the nutritional problems of the first 1000 days of life which are unbalanced, child and maternal factors greatly influence the incidence of stunting. Objective: this study is examines the relationship between gender, birth weight and maternal age with the risk of stunting in children under five. Method: A systematic review was conducted from three database, PubMed, Scopus, and ProQuest. Keyword used were “sex of child” or “gender of child” and “birth weight” and “maternal age” and “stunting”, articles published in the last five years from 2019 to 2023 in English. Article screening from titles and abstracts followed by full text review to assess article eligibility. The research design was cross-sectional and case-control studies. Article analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and JBI tool was used to assess the quality of studies. Results: From 686 article records screened, seven articles included review in this study. There are three factors that influence the occurrence of stunting, namely child's gender, child's birth weight and maternal age. Boy was more susceptible to stunting than girl births. Children with small birth weight were at risk of stunting and death, common causes due to poor health, disabilities, and maternal nutrition lifestyle. Furthermore, maternal age <18 years and >34 years increase the risk of malnutrition and death of children at birth. Conclusions: There is correlation child gender, birth weight, and maternal age on the risk of stunting. Increased knowledge and improved nutrition from pregnancy to birth contibute to improving the quality of life of children and reducing the risk of stunting.